Color change study of copper oxide (CuO) films. using image processing techniques (Journal of the College of Basic Education, 2023)
Thin films of CuO with different thickness were prepared utilizing chemical spray pyrolysis technique. Colour properties were studied from during the study of the results of digital images of these films , where getting on them by using optical microscope and digital camera connected with computer , showed clear difference of the colour of prepared films with different thickness , where we apply many image processing techniques .